Mice lacking mitochondrial ferritin are more sensitive to doxorubicin-mediated cardiotoxicity - Maccarinelli, Federica (Springer Berlin Heidelberg, 2014)
ABSTRACT: Mitochondrial ferritin is a functional ferritin that localizes in the mitochondria. It is expressed in the testis, heart, brain, and cells with active respiratory activity. Its overexpression in cultured cells protected against oxidative damage and reduced cytosolic iron availability. However, no overt phenotype was described in mice with inactivation of the FtMt gene. Here, we used the doxorubicin model of cardiac injury in a novel strain of FtMt-null mice to investigate the antioxidant role of FtMt. These mice did not show any evident phenotype, but after acute treatment to doxorubicin, they showed enhanced mortality and altered heart morphology with fibril disorganization and severe mitochondrial damage. Signs of mitochondrial damage were present also in mock-treated FtMt(−/−) mice. The hearts of saline- and doxorubicin-treated FtMt(−/−) mice had higher thiobarbituric acid reactive substance levels, heme oxygenase 1 expression, and protein oxidation, but did not differ from FtMt(+/+) in the cardiac damage marker B-type natriuretic peptide (BNP), ATP levels, and apoptosis. However, the autophagy marker LC3 was activated. The results show that the absence of FtMt, which is highly expressed in the heart, increases the sensitivity of heart mitochondria to the toxicity of doxorubicin. This study represents the first in vivo evidence of the antioxidant role of FtMt. KEY MESSAGE: Mitochondrial ferritin (FtMt) expressed in the heart has a protective antioxidant role. Acute treatment with doxorubicin caused the death of all FtMt(−/−) and only of 60 % FtMt(+/+) mice. The hearts of FtMt(−/−) mice showed fibril disorganization and mitochondrial damage. Markers of oxidative damage and autophagy were increased in FtMt(−/−) hearts. This is the first in vivo evidence of the antioxidant role of FtMt. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00109-014-1147-0) contains supplementary material, which is available to authorized users.